Clinical reasoning - A guide to improving teaching and practice. - Linn A; Khaw C; Kildea H; Tonkin A (Australian Family Physician)
Background The process of clinical reasoning is undertaken by all clinicians, often automatically, and is the cognitive process that underlies diagnosis and management of a patient's presenting problem. The teaching of clinical reasoning can pose a challenge to the clinical teacher. Objective This article reviews the process of clinical reasoning and provides the teacher with a framework to teach clinical reasoning to students and junior doctors. Discussion By considering clinical reasoning as a skill to be learnt rather than a concept to be understood, a framework for teaching this skill can be developed. The learner initially observes a consultation by the teaching clinician, followed by the teacher explaining the reasoning processes used including hypothesising, hypothesis testing, re-analysis and differential diagnosis. The student then comments on the reasoning of the teacher in a subsequent consultation, followed by feedback from the teacher on the student's reasoning in a third consultation.